2021
DOI: 10.3390/vaccines9050529
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Influenza Vaccination and COVID-19 and Its Outcomes: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Influenza could circulate in parallel with COVID-19. In the context of COVID-19, some studies observed inverse associations between influenza vaccination and SARS-CoV-2 infection and clinical outcomes, while others did not. We conducted a meta-analysis to assess the association between influenza vaccination and SARS-CoV-2 infection and clinical outcomes, aiming to provide evidence for COVID-19 prevention and vaccination promotion. We searched four databases from inception to 10 March, 2021. Random effects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 47 publications
6
59
1
2
Order By: Relevance
“…Moreover, by exerting the so-called "trained immunity" effect (i.e., by boosting the innate immune system), IV may reduce the incidence of some COVID-19-related outcomes. A systematic review and meta-analysis by Wang et al [48] recently demonstrated a 14% (aOR 0.86, 95% CI: 0.81-0.91) reduction in the odds of being positive to SARS-CoV-2 in subjects vaccinated against influenza, as compared with non-vaccinated subjects. This argument could also be used to increase IV acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by exerting the so-called "trained immunity" effect (i.e., by boosting the innate immune system), IV may reduce the incidence of some COVID-19-related outcomes. A systematic review and meta-analysis by Wang et al [48] recently demonstrated a 14% (aOR 0.86, 95% CI: 0.81-0.91) reduction in the odds of being positive to SARS-CoV-2 in subjects vaccinated against influenza, as compared with non-vaccinated subjects. This argument could also be used to increase IV acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination still remains the best approach to mitigate disease burden caused by respiratory viral infection. Current vaccines against influenza and SARS-CoV2 infections are mainly administered via the systemic route, which induces strong systemic but typically weak mucosal immune responses [ 141 , 142 , 143 , 144 ].…”
Section: T Rh Cells As a Potential Target For Mucosal Vaccine Against Respiratory Viral Infectionmentioning
confidence: 99%
“…Although preventable, both seasonal influenza and pneumococcal diseases still cause a significant amount of severe cases and death each year [ 6 , 7 , 8 , 9 ].…”
Section: Risk Of Mortality For Preventable Respiratory Infectionsmentioning
confidence: 99%
“…Seasonal influenza epidemics implies a well-documented burden on healthcare systems during winter time and result in considerable mortality with estimates of 250,000 – 500,000 death annually [ 5 ]. Older age and comorbidities accounted as the most common risk factors for influenza-related complications including mortality [ 6 , 7 ].…”
Section: Risk Of Mortality For Preventable Respiratory Infectionsmentioning
confidence: 99%
See 1 more Smart Citation